HUBUNGAN GAYA KEPEMIMPINAN TRANSFORMASIONAL DENGAN EFEKTIVITAS KINERJA PADA PERGURUAN TINGGI SWASTA DIY - Eni Rohyati & FX Wahyu Widiantoro (LPPM Universitas Proklamasi 45, 2017)
Objective of this research was to verify the relationship between the transformationalleadership style and work performance among employees. Fifty middle managers were involvedin this research. They were recruited randomly from 5 private universities in Yogyakarta. Thisresearch revealed that those managers’ work performances were positively correlated withtheir superior’s transformational leadership style, rxy = .713 (p = .00). A limitation of thisresearch was related to the accreditation score of the university. In fact, the organization’saccreditation score reflects the leadership style of the owner / employer. The higher scoreindicates that the superior is really appreciated by his / her employees. It seems he / she hasapplied the transformational leadership style. Unfortunately, this research sample does notconsider the accreditation score. Therefore the sample was less likely to be homogenous.Key words: work performance, transformational leadership style.